Menorrhagia management options. - Doherty, L. (Ulster Medical Society, 1995)
A prospective study of the management of menorrhagia in new patients presenting to gynaecological outpatients was undertaken at four centres in Northern Ireland and two in Great Britain. 325 patients were enrolled, the majority of whom (87%) had severe menorrhagia. Patients in all six centres were similar in relation to age, marital status, parity, use of contraception and severity of symptoms. 62% of the patients were managed medically, improved and were discharged. The rates of surgical intervention, in particular in women aged less than 40, appeared higher in the Northern Ireland hospitals than Great Britain. There is a need to review and audit current practices in the management of menorrhagia.